2014
DOI: 10.1111/cas.12504
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α promotes the lymphangiogenesis of gallbladder carcinoma through nuclear factor‐κB‐mediated upregulation of vascular endothelial growth factor‐C

Abstract: Vascular endothelial growth factor (VEGF)-C is an important lymphangiogenic factor involved in the lymphangiogenesis of gallbladder carcinoma (GBC) and the lymph node metastasis of the tumor. Tumor necrosis factor (TNF)-α, a key inflammatory cytokine responding to chronic inflammation of GBC, has been reported to stimulate the expression of VEGF-C in some nonneoplastic cells. But whether TNF-α promotes the expression of VEGF-C in GBC has yet to be determined. Therefore, in the present study, the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 38 publications
4
58
0
1
Order By: Relevance
“…Transcription factors control the expression of a given gene by serving as integration centers of different signaling cascades26. Many transcription factors regulate VEGF transcription and expression272829. Daft et al 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors control the expression of a given gene by serving as integration centers of different signaling cascades26. Many transcription factors regulate VEGF transcription and expression272829. Daft et al 27.…”
Section: Discussionmentioning
confidence: 99%
“…One report demonstrated that hyperglycemia significantly increased the binding of the transcription factor Sp1 to the VEGF-A promoter28. Du et al 29. used site-directed mutagenesis, electrophoretic mobility shift assay (EMSA) and ChIP technologies to determine the nuclear factor (NF)-κB binding site on the VEGF-C promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Such mediators include growth factors fibroblast growth factor-2 (FGF-2) [129], platelet-derived growth factor-BB (PDGF-BB) [130,131], nerve growth factor (NGF) [132], insulin-like growth factor-1 (IGF-1) and -2 [133], and hepatocyte growth factor (HGF) [134]; inflammatory cytokines interleukin-1 β (IL-1β) [135,136] and tumor necrosis factor- α (TNF-α) [135137]; and other non-traditional signaling molecules lipid sphingosine-1-phosphate [138], cyclooxygenase 2 (Cox2), and EP3/4 [139]. A role for integrins in lymphangiogenesis is also emerging with evidence of binding of VEGF-A, -C, and -D to lymphatic endothelial-specific integrin-α9β1 [140,141].…”
Section: Lymphangiogenesismentioning
confidence: 99%
“…While each of these factors does induce new lymphatic vessel growth, not all lymphangiogenesis is created equal; a study of corneal lymphangiogenesis in response to VEGF-A, VEGF-C, or FGF-2-loaded micropellets has revealed differences in both structure and function of lymphatic vessels and the proportion of blood to lymphatic vessels induced by these growth factors [142]. In the case of indirect stimulation of lymphangiogenesis, paracrine signals such as IL-1β [135,136] and TNF-α [135137] can drive increased expression of the VEGFs, most notably VEGF-C. This likely occurs through activation of the NFκB promoter to induce VEGF-C expression [137].…”
Section: Lymphangiogenesismentioning
confidence: 99%
See 1 more Smart Citation